The relationship between fibroblast growth factor 21 with biochemical parameters, anthropometric measurements and dietary intake in type 2 diabetic patients - Mirzaee, Elham; Payahoo, Laleh; Ghoreishi, Zohreh; Razmi, Hamireza; Amirpour, Mehdi (Progress in Nutrition, 2023)
Background: Fibroblast growth factor-21 (FGF-21), as a novel cytokine, plays an important role in the improvement of glucose and lipid metabolism via different metabolic pathways. Therefore, the aim of this study to investigate the relationship between FGF-21 and metabolic profile parameters in patients with type 2 diabetes mellitus (T2DM) compared to healthy controls.Methods: In this cross-sectional study, 85 patients with T2DM and 79 healthy subjects were recruited. Anthropometric measurements, dietary intake and biochemical measurements were assessed for all participants.Results: Serum levels of FGF-21 were negatively associated with hip circumference (HC) (β= -0.267, p= 0.038) and dietary proteins (β = -0.273, p= 0.005) in healthy subjects. Moreover, dietary carbohydrate intake was inversely associated with FGF-21 (β= -0.183, p=0.041) in the total population. Also, serum levels of total cholesterol (TC), low density lipoprotein-cholesterol (LDL-C) and fasting blood sugar (FBS) in diabetic patients were significantly higher than those in healthy subjects (p